Salinity-Induced Changes of Photosynthetic Performance, Lawsone, VOCs, and Antioxidant Metabolism in Lawsonia inermis L. - Basma Najar; Laura Pistelli; Ilaria Marchioni; Luisa Pistelli; Beatrice Muscatello; Marinella De Leo; Andrea Scartazza (Plants, 2020)
The present study aimed to elucidate the salinity influence on the bioactive metabolites of Lawsonia inermis L. (henna) plants. Young henna plants were cultivated under salinity stress with two NaCl concentrations (75 mM and 150 mM) in controlled environmental conditions and the leaves were investigated to check their adaptative responses. The modulation of photosynthetic performance to salinity stress was demonstrated by gas exchange and chlorophyll fluorescence parameters. The partial stomatal closure triggered an enhanced water-use efficiency, and a proline accumulation was observed, leading to an osmotic adjustment. The increased capacity to dissipate the excess excitation energy at photosystem II as heat was associated with changes in chlorophylls, anthocyanins, and carotenoids. The higher antioxidant activity at 150 mM salt level suggested its scavenger role on reactive oxygen species (ROS) dissipation and photoprotection. The reduced CO2 uptake and the higher metabolic costs necessary to sustain the henna tolerance mechanism against high NaCl concentration negatively affected lawsone production. Leaf volatile organic compounds (VOCs) showed changes in the amount and composition of VOCs with increasing salinity level. Overall, this study revealed efficient physiological and biochemical adaptations of henna leaves to salt stress despite an altered production of important economic metabolites such as lawsone.